Time Trends in the Prevalence of Cancer and Non-Cancer Diseases among older U.S. adults: Medicare-based analysis - Akushevich, Igor (Exp Gerontol, 2018)
Longer lifespan is accompanied by a larger number of chronic diseases among older adults. Because of a growing proportion of older adults in the U.S., this brings the problem of age-related morbidity to the forefront as a major contributor to rising medical expenditures. We evaluated 15-year time trends (from 1998 to 2013) in the prevalence of 48 acute and chronic non-cancer diseases and cancers in older U.S. adults aged 65+ and estimated the annual percentage changes of these prevalence trends using SEER-Medicare and HRS-Medicare data. We found that age-adjusted prevalence of cancers of kidney, pancreas, and melanoma, as well as diabetes, renal disease, limb fracture, depression, anemia, weight deficiency, dementia/Alzheimer’s disease, drug/medications abuse and several other diseases/conditions increased over time. Conversely, prevalence of myocardial infarction, heart failure, cardiomyopathy, pneumonia/influenza, peptic ulcer, and gastrointestinal bleeding, among others, decreased over time. There are also diseases whose prevalence did not change substantially over time, e.g., a group of fast progressing cancers and rheumatoid arthritis. Analysis of trends of multiple diseases performed simultaneously within one study design with focus on the same time interval and the same population for all diseases allowed us to provide insight into the epidemiology of these conditions and identify the most alarming and/or unexpected trends and trade-offs. The obtained results can be used for health expenditures planning for growing sector of older adults in the U.S.